2001
DOI: 10.1186/1297-9686-33-3-209
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the effects of genes affecting quantitative traits in livestock

Abstract: -Meta-analysis of information from quantitative trait loci (QTL) mapping experiments was used to derive distributions of the effects of genes affecting quantitative traits. The two limitations of such information, that QTL effects as reported include experimental error, and that mapping experiments can only detect QTL above a certain size, were accounted for. Data from pig and dairy mapping experiments were used. Gamma distributions of QTL effects were fitted with maximum likelihood. The derived distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
208
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(225 citation statements)
references
References 27 publications
14
208
0
3
Order By: Relevance
“…The meta-analysis of the effect sizes indicated that some chromosomal regions explain a relatively significant proportion of variation in milk production traits. Based on results from QTL mapping experiments in dairy cattle, Hayes and Goddard [29] fitted gamma distributions of QTL effects. These were moderately leptokurtic, consistent with a few genes of large effect and many of small effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The meta-analysis of the effect sizes indicated that some chromosomal regions explain a relatively significant proportion of variation in milk production traits. Based on results from QTL mapping experiments in dairy cattle, Hayes and Goddard [29] fitted gamma distributions of QTL effects. These were moderately leptokurtic, consistent with a few genes of large effect and many of small effect.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis makes the literature review process more transparent, compared with traditional narrative reviews where it is often not clear how the conclusions follow from the data examined [17]. The application of meta-analysis to QTL detection is recent [26,29]. The combining of the results across studies can provide a more precise and consensus estimate of the location of a QTL and its effect as compared with any single study.…”
Section: Meta-analysis Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Although in livestock it is not a usual analytical tool it is in medical research, perhaps because of the widely recognised importance of being systematic when reviewing the evidence available on the benefits and risks of medical decisions [54]. Only recently, meta-analysis has been introduced to study genes of interest in livestock [15,19,23] although not in the context of candidate gene studies.…”
Section: Introductionmentioning
confidence: 99%